2010
DOI: 10.1177/1359786810385489
|View full text |Cite
|
Sign up to set email alerts
|

Review: Cancer and schizophrenia: is there a paradox?

Abstract: People with schizophrenia are more likely to die prematurely than the general population from both suicide and physical ill health. Published studies examining the incidence of cancer in schizophrenia patients report increased, reduced or similar incidence compared with the general population. Older studies tended to report lower incidence rates which fuelled speculation as to the biological and other mechanisms for this protective effect. Furthermore, mortality rates in patients with schizophrenia appear high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 100 publications
1
69
1
2
Order By: Relevance
“…This is confirmed by a disproportion in mortality from cardiac infarction or cancer in schizophrenia patients and in people without such diagnosis, unfavourable for the former, despite similar prevalence of these disorders (Kisely et al 2008, Hodgson et al 2010, Crump et al 2013). Furthermore, in people who died due to above causes, these disorders were significantly less often diagnosed in schizophrenia patients during their life, and this may indicate lower availability of screening tests and modern diagnostic methods.…”
Section: Discussionmentioning
confidence: 90%
“…This is confirmed by a disproportion in mortality from cardiac infarction or cancer in schizophrenia patients and in people without such diagnosis, unfavourable for the former, despite similar prevalence of these disorders (Kisely et al 2008, Hodgson et al 2010, Crump et al 2013). Furthermore, in people who died due to above causes, these disorders were significantly less often diagnosed in schizophrenia patients during their life, and this may indicate lower availability of screening tests and modern diagnostic methods.…”
Section: Discussionmentioning
confidence: 90%
“…The link between schizophrenia therapy and TLK inhibition is an interesting possibility because if the TLK-inhibiting properties of these drugs are effective against BCA, then one would expect that women who had been prescribed these drugs might display 1) a lower incidence of BCA compared to those who did not take the drugs and/or 2) an improved outcome after BCA diagnosis. While women with schizophrenia have multiple risk factors for BCA that might lead to expectations of a substantially increased risk (smoking, obesity, low exercise, poor diet, treatment-induced hyperprolactinemia), results of a systematic review of such studies 17 revealed that the incidence is decreased, similar, or only slightly increased from that of the general population. Various hypotheses have been proposed for such findings, including protective genetic effects [52][53][54][55] and antitumor properties of neuroleptics.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is well known to increase the incidence of various types of cancer, including oral, stomach, liver, bladder, and lung cancer [2]; of these cancers, lung cancer has the highest mortality rate [3]. In addition, smoking and other cancer-related risk factors, such as alcohol abuse, obesity, and poor diet, are more common in schizophrenia patients than in the general population [4]. However, patients diagnosed with schizophrenia have a lower incidence of cancer than that observed in the general population [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%